A pharmacodynamic comparison of a personalized strategy for anti-platelet therapy versus ticagrelor in achieving a therapeutic window. (15th October 2015) - Malhotra, Nikita; Abunassar, Joseph; Wells, George A.; McPherson, Ruth; Fu, Angel; Hibbert, Benjamin; Labinaz, Marino; Le May, Michel; Dick, Alexander; Glover, Chris; Froeschl, Michael; Marquis, Jean-François; et al.
Abstract: Background: A therapeutic window in antiplatelet treatment has been associated with concurrent lowering of bleeding and ischemic risks. Prasugrel and ticagrelor provide potent platelet inhibition, but may increase bleeding. No study has evaluated a personalized therapy with selective use of novel P2Y12 inhibitory agents compared to empiric ticagrelor use. The objective of this study was to compare a personalized anti-platelet therapy strategy to empiric ticagrelor in achieving a therapeutic window. Methods: Using the CAPITAL registry, we performed a retrospective analysis to evaluate a personalized anti-platelet therapy (PAT) strategy, using a pharmacogenetic approach, and compared it to empiric ticagrelor. In the PAT group, carriers of CYP2C19*2 received prasugrel and non-carriers received clopidogrel. The primary outcome was the proportion of patients within a validated therapeutic window, after a steady state treatment (≥ 48 h) of antiplatelet therapy, as measured by a P2Y12 reaction unit (PRU) > 85 and < 208. Results: Of 199 patients with platelet function measurements, 150 received PAT, while 49 received ticagrelor. Significantly more patients on PAT achieved the primary outcome (50.0% vs. 4.1%, p < 0.0001). This was predominantly driven by an increase in low on-treatment reactivity with ticagrelor (95.9% vs. 37.3%, p < 0.0001). Multivariable analysis demonstrated PAT to be the strongest predictor of achieving PRU values within the therapeutic window (odds ratio 20.27; 95% CI: 4.33–94.82, p = 0.0001). Conclusion: Patients treated with PAT were more likely to achieve a therapeutic window compared to a strategy of ticagrelor. Future prospective evaluation of novel PAT strategies will be required to prove clinical utility.